2021
DOI: 10.1111/plb.13226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV‐B radiation on growth, flavonoid and podophyllotoxin accumulation, and related gene expression in Sinopodophyllum hexandrum

Abstract: Sinopodophyllum hexandrum is an alpine medicinal plant that produces the anticancer compound podophyllotoxin (PPT). Although a positive relationship between PPT content and altitude has been proved and low temperature enhances plant growth and PPT accumulation has also been revealed, the role of UV radiation in regulating growth and PPT accumulation is still unclear • In this study, morphophysiological traits, metabolites content and related genes expression were investigated by exposing S. hexandrum seedlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…For example, supplemental UV-B radiation significantly improved the activities of phenylalanine ammonia-lyase (PAL), cinnamyl alcohol dehydrogenase (CAD), 4-coumaric acid: CoA ligase (4CL), CHI, and dihydroflavonol 4-reductase (DFR), and enhanced the contents of flavonoids and phenolicp0s in the leaves of C. forskohlii and Withania somnifera Agrawal, 2014, 2015). In Sinopodophyllum hexandrum, treatment with UV-B (1.07 W•m −2 ) significantly decreased the content of podophyllotoxin as well as transcript levels of 12 related genes, including cinnamic acid 3-hydroxylase (C3H), caffeoyl-CoA O-methyltransferase (CCoAMT), cinnamoyl-CoA reductase (CCR), CAD, dirigent protein oxidase (DPO), pinoresinol-lariciresinol reductase (PLR), secoisolariciresinol dehydrogenase (SDH), cytochrome P450 719A23 (CPY719A23), O-methyltransferase3 (OMT3), cytochrome P450 71CU1 (CYP71CU1), OMT1, and 2-oxoglutarate/Fe(II)-dependent dioxygenase (2-ODD; Lv et al, 2021). In Glycyrrhiza uralensis, Zhang et al (2018a) showed that UV-B radiation stimulated the expression of several genes involved in the flavonoid biosynthetic pathway, such as cinnamic acid 4-hydroxylase (C4H), PAL, CHS, CHI, and FLS.…”
Section: Polyphenolsmentioning
confidence: 99%
“…For example, supplemental UV-B radiation significantly improved the activities of phenylalanine ammonia-lyase (PAL), cinnamyl alcohol dehydrogenase (CAD), 4-coumaric acid: CoA ligase (4CL), CHI, and dihydroflavonol 4-reductase (DFR), and enhanced the contents of flavonoids and phenolicp0s in the leaves of C. forskohlii and Withania somnifera Agrawal, 2014, 2015). In Sinopodophyllum hexandrum, treatment with UV-B (1.07 W•m −2 ) significantly decreased the content of podophyllotoxin as well as transcript levels of 12 related genes, including cinnamic acid 3-hydroxylase (C3H), caffeoyl-CoA O-methyltransferase (CCoAMT), cinnamoyl-CoA reductase (CCR), CAD, dirigent protein oxidase (DPO), pinoresinol-lariciresinol reductase (PLR), secoisolariciresinol dehydrogenase (SDH), cytochrome P450 719A23 (CPY719A23), O-methyltransferase3 (OMT3), cytochrome P450 71CU1 (CYP71CU1), OMT1, and 2-oxoglutarate/Fe(II)-dependent dioxygenase (2-ODD; Lv et al, 2021). In Glycyrrhiza uralensis, Zhang et al (2018a) showed that UV-B radiation stimulated the expression of several genes involved in the flavonoid biosynthetic pathway, such as cinnamic acid 4-hydroxylase (C4H), PAL, CHS, CHI, and FLS.…”
Section: Polyphenolsmentioning
confidence: 99%
“…Flavonoids content was determined using the NaNO 2 -AlCl 3 -NaOH method [ 43 , 44 ]. Briefly, the extracts (2.5 mL) were added into ddH 2 O (2 mL) and NaNO 2 (5% w / v , 0.3 mL); after oscillation, and AlCl 3 (10% w / v , 0.3 mL) was added and reacted at 22 °C for 1 min; then, NaOH (1.0 mol/L, 2 mL) was added to stop the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The extracts were increased to 20 mL with ethanol (95% v / v ). Total flavonoids content was measured according to a NaNO 2 -AlCl 3 -NaOH method [ 51 , 52 ]. Briefly, extracts (150 μL) were added in ddH 2 O (2 mL) and NaNO 2 (5% w / v , 0.3 mL).…”
Section: Methodsmentioning
confidence: 99%